ANTIOXIDANT ACTIVITY AND PROTECTIVE EFFECT OF THE PHENOLIC FRACTION FROM OLIVE OIL AGAINST LIPID PEROXIDATION INDUCED BY H2O2 AND FECL3 - Fatiha Abdellah1’2, Khaled Hamden2, Tayeb Silarbi1’2, Noura Ayad 1, Laid Boukraa1, Si Mohamed Hammoudi1 ,Rachida Benaraba1 (Chelonian Research Foundation, 2024)
Hydrogen peroxide (H2O2) and iron can be toxic to human cells and produce highly reactive oxygen species (ROS) such as hydroxyl radicals (OH•). These ROS can damage cellular components like DNA, proteins, and lipids, leading to cell injury or death. Olive oil is one of the most important components of the Mediterranean diet characterized by many therapeutic proprieties and health protective effects, mainly attributed to its high content of monounsaturated oleic acid, vitamin and polyphenolic compounds. The aim of this study was to evaluate the in vitro antioxidant activity of the phenolic extracts of two Algerian olive oil varieties (Chemlal and Sigoise) and to determinate their protective effect against lipid peroxidation. We have used Folin-Ciocalteu reagent method to estimate the phenolic content of the studied extracts. The antioxidant activity was determined using three different antioxidant assays (DPPH scavenging activity, reducing power and hydrogen peroxide scavenging assay). The protective effect of olive oil extract against lipid peroxidation was evaluated in an in vitro model of rat liver homogenates through the production of TBARS. The quantitative analysis results showed that the phenolic extracts of Algerian olive oil are rich in phenolic compounds mostly flavonoids, with the highest content found in Chemlal oil (366.095± 1.01 mg GAE/Kg for polyphenols and 79.065± 0.84 mg QE/Kg for flavonoids). Moreover, the studied extracts showed very important anti-free radical activity and reducing power, wherein Chemlal oil exhibited the highest antioxidant activity. The tested extracts demonstrated a strong protective effect against lipid peroxidation, with Chemlal olive oil showing the highest protective effect. These findings confirmed the medicinal use of Algerian olive oils as natural agents in food and pharmaceutical industries Keywords: olive oil, polyphenols, oxidative stress, biological activities.